Physiology of Starvation and Refeeding Syndrome - Choudhary, Raghuveer; Chawala, Vinode Kumar; Kumar, Jayant; Rathore, Raj Kumar (Journal of Bangladesh Society of Physiologist, 2011)
Refeeding syndrome represents a series of metabolic complications that sometimes results by provision of nutrients, primarily carbohydrate, to a patient in a nutritionally compromised state. Refeeding syndrome is associated with hypophosphatemia, hypokalemia and hypomagnesaemia, fluid retention and vitamin deficiencies including thiamin are also of concern. If severe, refeeding syndrome may result in respiratory, cardiac, and neuromuscular dysfunction, especially in the stressed, elderly, or severely malnourished patient. This article discuss the physiology of starvation and the pathophysiology behind refeeding syndrome, identify the patients at greatest risk, and provide practical tips for prevention. As increased awareness and understanding of refeeding syndrome may help, prevent further such incidents and clinicians learn to recognize patients at risk and avoid overaggressive nutrition support regimes. Key words: Starvation; Refeeding Syndrome DOI: 10.3329/jbsp.v5i2.6785 J Bangladesh Soc Physiol. 2010 December; 5(2): 101-110